Anticipated Children and Educational Investment: Evidence from the One-Child Policy in China - Eva Raiber (ZBW - Leibniz Information Centre for Economics, 2021)
Does the number of future anticipated children affect educational investment in parents-to-be? In theory, anticipated children can affect the returns to education, the resources available for family consumption, and the incentives for pre-marital investment. Changes in the eligibility criteria for second-child permits during the one-child policy in China provide province-, time- and group-specific variation in the cost of having a second child. I first show that second-child permits have a strong positive effect on the likelihood of having a second child. I then investigate changes in the eligibility rules when individuals are about the finish middle school. I find that fulfilling an eligibility criterion at secondary school age increases the likelihood of enrolling in senior middle school. The effect is concentrated among those planning with only one child when not eligible, indicating that anticipating another child increases educational investment. The estimates are more precise for men who do not seem to suffer from a child penalty in the labor market and usually have a higher income than their wives, suggesting that the high costs of raising children can be a reason for increased educational investment.
Keywords: I25; I26; J13; 330; Fertility; Schooling Investment; Family Planning; China